Clausal Ellipsis in the Dialogue of the Movie “To All the Boys: Always and Forever” - Esa Cahyani, Ni Putu; Suastini, NI Wayan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Ellipsis is a part of discourse that studies about omission of words in a sentence or utterance to avoid repetition. This study focuses on finding the type of clausal ellipsis and the reference parts of clausal ellipsis omitted in the dialogue of the movie “To All the Boys: Always and Forever”. This study expects to aid students in learning clausal ellipsis and provide insight into clausal ellipsis and its reference parts. This study used Halliday and Hasan's theory (1976) to determine the type of clausal ellipsis. The data were collected by observation method and analyzed use descriptive qualitative method. Based on results, the clausal ellipsis is found with total 88 data; 29 data of modal ellipsis, 26 data of propositional ellipsis, 33 data of question-answer ellipsis. The use of question-answer ellipsis was widely used in the movie dialogue because the casts wanted to give a direct response to the questions without implication due to the relation and situation between the casts in the movie was informal.